‘I Would Like to be a Healthy Egoist’: A Case of Ceratostigma willmottiana - Collins, Deborah (Homœopathic Links, 2017)
This is the case of a woman suffering from depression and burnout, dating back to a childhood where she felt that she had to put all her own desires and ambitions aside due to the family situation: a drunken father and a mother who cared for him but had little time for her children. It was only with the help of the Plant theory that a suitable remedy was found.
Keywords: Burnout; Depression; Plant theory; Scholten; Ceratostigma willmottiana